Vascularized skin tissue models featuring adipose cell spheroid-laden GelMA hydrogels - Dongjin Lee; Sangmin Lee; Jeongbok Lee; Dahong Kim; Hyunseok Kwon; Junhyoung Ahn; Hyungjun Lim; Jae Jong Lee; Heungsoo Shin; Su A Park (Materials Today Bio)
The multifaceted tissue interplay between skin and adipose structures is increasingly recognized to play crucial roles in antimicrobial defense, hair cycling, wound healing, and thermogenesis. However, the technical challenges associated with the development of an in vitro model of such complex tissues include the difficulties of integrating tissues with diverse characteristics. Here, we present a method using a gelatin methacryloyl (GelMA) hydrogel to establish a microenvironment that hosts connected composite tissues: a vascularized skin layer and a subcutaneous adipose layer. When adipogenesis proceeded in 3T3-L1 cell spheroid-laden three-dimensional (3D)-printed polycaprolactone (PCL) scaffolds after 1- and 2-min exposure to ultraviolet (UV) light, we observed that adipose tissue, the physical properties of which had been optimized by 1-min UV exposure, facilitated the migration and proliferation of 3T3-L1 cells. Furthermore, a notable enhancement in adipogenesis was apparent. Subsequently, using advanced 3D printing technology, we meticulously crafted a 3D vascularized skin layer by integrating microgels with human umbilical vein endothelial cells (HUVECs) and fibroblasts. HUVEC cells growing on the surface of the microgel exhibited a 3D structure that allowed vascular cells to become concentrated in the microgel area much more efficiently than in 2D culture. Three-dimensional printing allows efficient mass production, removing challenges that cannot be easily addressed via in vivo experiments. In the immediate future, we will simulate complex pathological conditions such as burns, psoriasis, and atopy. Our approach will facilitate the discovery of useful treatments for these conditions.